2014
DOI: 10.20453/reh.v15i1.1969
|View full text |Cite
|
Sign up to set email alerts
|

Resistencia a la fractura frente a carga estática transversal en piezas dentarias restauradas con espigo-muñón colado, postes de fibra de carbono y de aleación de titanio

Abstract: El propósito del presente estudio fue determinar la resistencia a la fractura frente a cargaestática transversal de piezas dentarias tratadas endodonticamente, restauradas con espigomuñóncolado, postes de fibra de carbono(C-Post®, ©Bisco Inc) y postes de aleación de titanio(Parapost®, ©Coltène/Whaledent Inc.). Se utilizó el adhesivo All Bond 2® (©Bisco, Inc) comomaterial adhesivo y el cemento de resina Duolink® (©Bisco Inc) para cementar los postes. Laprueba de anova unifactorial encontró que las piezas dentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Additionally, this type of reconstruction can better withstand transverse static forces when compared to adhesive posts, this is also due to the intrinsic adaptation of the casting with root anatomy. 24 Nevertheless, in the distribution of assessed groups, NiCr alloy was found in greater proportion in the unfi lled posts group than in the fi lled post group. This latter group was mostly composed of fi berglass posts; this probably might have influenced results since metallic alloys are more resistant to compressive forces than fi berglass.…”
Section: Este Documento Es Elaborado Por Medigraphicmentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, this type of reconstruction can better withstand transverse static forces when compared to adhesive posts, this is also due to the intrinsic adaptation of the casting with root anatomy. 24 Nevertheless, in the distribution of assessed groups, NiCr alloy was found in greater proportion in the unfi lled posts group than in the fi lled post group. This latter group was mostly composed of fi berglass posts; this probably might have influenced results since metallic alloys are more resistant to compressive forces than fi berglass.…”
Section: Este Documento Es Elaborado Por Medigraphicmentioning
confidence: 90%
“…This latter group was mostly composed of fi berglass posts; this probably might have influenced results since metallic alloys are more resistant to compressive forces than fi berglass. 24,25 Authors such as Saupe et al, 17 Katebzadeh et al, 18 Liang et al, 19 Wu et al, 20 and Fukui et al, 26 concluded that the use of metallic posts with resin increased resistance to fracture, and that this difference was statistically significant when compared to unfilled posts. This could be explained by the fact that used filling material increased root wall thickness of the tooth, creating a more resistant surface which absorbs and distributes forces transmitted during chewing movements, more uniformly than that achieved by metallic materials, offering thus better prognosis in restoration function.…”
Section: Este Documento Es Elaborado Por Medigraphicmentioning
confidence: 99%